Skip beat! 50 - Nakamura, Yoshiki; Kimura, Tomo (Shojo beat manga., 2025)
"Kyoko Mogami followed her true love Sho to Tokyo to support him while he made it big as an idol. But he's casting her out now that he's famous! Kyoko won't suffer in silence--she's going to get her sweet revenge by beating Sho in show biz! Welcome to Hollywood! Kyoko is thrilled as the Route project takes off in sunny California. But even the excitement of exploring a real American movie studio isn't enough to distract her from the current calamity--when Ren says "Kyoko," she can tell he means her real name and not her stage name. How can Kyoko act normal when he keeps doing that?!"--Back cover.